Assessment of body composition in hemodialysis patients with DKD and hemodialysis patients with non-DKD - XU Yuan-zhao; QI Ai-rong; XU Cai; ZHOU Li; ZENG You-jia (Linchuang shenzangbing zazhi)
Objective To understand the difference of body composition between hemodialysis patients with diabetic kidney diseases(DKD) and hemodialysis ones with non-DKD, and evaluate the balance of body fluid and phase angle in different hemodialysis patients. Methods A total of 85 hemodialysis patients in Shenzhen Municipal TCM Hospital were selected, and divided into DKD-hemodialysis patient group(31 cases) and non-DKD hemodialysis patient group(54 cases) based on their basic kidney diseases. The body composition analyzer was used to measure the body composition parameters such as extracellular fluid ratio and phase angle, and to conduct comparison between the two groups. Results In comparison between DKD-hemodialysis patients and non-DKD-hemodialysis ones, there was no significant difference in gender, age, height and ultrafiltration volume(P>0.05). Mean blood pressure, and interdialytic body weight and dry body weight with the DKD group were significantly higher than those with the non-DKD group, but phase angles of each segment with the DKD group were lower than that with the non-DKD group(P<0.05). In addition, extracellular fluid content and fluid contents in the whole body and each segment with the DKD group were higher than those with the non-DKD group(P<0.05). Conclusions Compared to the hemodialysis patients with non-DKD, the hemodialysis ones with DKD have more severe body fluid distribution abnormality and hypertension, and significantly increased risk for malnutrition.